Pengaruh Fee Audit, Rotasi Kap, Ukuran Kap Dan Audit Tenure Terhadap Kualitas Audit (Studi Empiris Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2012-2015) - Utami, Dyah Rini; , Drs. Atwal Arifin, Ak, M.Si, CA (2017)
The purpose of this study is to examine the influence of audit fee, rotation of KAP, size KAP, and audit tenure of audit quality. The analitical method applied in this research was the logistic regression. The population in this research is the banking companies listed in Indonesia Stock Exchange 2012-2015. Samples were selected by the purposive sampling. The obtained samples were 48 companies. The results showed that the audit fee, rotation of KAP, size KA, and audit tenure had no efeect toward audit quality. However the variabel audit tenure to proved that there is an effect toward audit quality.